Learning to play to learn in pediatric physical therapy - Håkstad, Ragnhild B.; Dusing, Stacey C.; Girolami, Gay L.; Øberg, Gunn Kristin; De Jaegher, Hanne (Frontiers in Psychology, 2025)
IntroductionPlay is a way for children to develop and learn about themselves in conjunction with the world. Using play as part of pediatric physical therapy is broadly recommended. This study investigates this integration of play and seeks to answer the research question: How do pediatric physical therapists (PPT) understand and manage embedding play in pediatric physical therapy with children aged 0–3?MethodsThis is a qualitative study in which we connect to an enactive theoretical framework. We interviewed 14 PPTs about their use of play, including video-elicited questions while viewing recordings of their therapy sessions. Our results were developed through an abductive thematic analysis.ResultsThe PPTs acknowledge play as a foundation of children’s learning and a vital component of physical therapy. They explain that play and therapy often co-exist and intertwine, but they also experience tensions when they strive to make play therapeutic. The PPTs find it taxing to engage in play with children who present with limited interaction and play skills, and voice concern for children who struggle to engage in interactional play.DiscussionTrusting play and letting play emerge through shared sense-making can resolve challenges and enable PPTs to discover new therapeutic opportunities. A child’s striving and overcoming of resistance can be infused with playfulness and make play thrive. We invite PPTs to experiment with the emerging opportunities and boundaries between therapy and play during treatment sessions. Respect for the child’s autonomy, attention to the child’s play experience, and repairs of interactional mismatches are crucial in this process. Therapeutic guidance and mutuality in interactions can empower children to learn to play to learn new skills and experience mastery as they explore and venture beyond what they already know.